Selected Rights for Persons with Disabilities to Become Presidents Associated with Legal and Spiritual Ability Conditions in Indonesia - Yoga Maulana Ibrahim (Khazanah Sosial, 2021)
Social rights for people with disabiltiy need to be protected, including political rights. The operationally political rights consist the right of chce and the right to be elect. The issue arises when people with disability have to face the term of physical and spiritual requirements for president, though neither are not entirely contradiction but technically the implementation of the health physically requirement threatens people with disability to be president. The study aims to explain the legal certainty of people with disability to be president linked to physical and spiritual requirement. This research aims to know physical and spiritual rule and limitations. This research uses normative juridical methods and analysis presented descriptively. This research uses conceptual approach, legal approach, and historical approach. The conclusion of this research is that there is no certainty for people with disability to be president until the government has the implementation which is regulate and affirm people with disabilty to pass the physical health and spiritual health requirements. The arrangement of formulation physical and spritual health was conducted by medical check up by the doctors team and decision made thorough them using medical approach and missed the social approach. While there is no clarity about the limits of form capable in physically and spiritual health to be president linked to people with disabilty as the extent of spectrum of ability.